Science studies and economics: An informal history - Eliot Roy Weintraub (Duke University, Center for the History of Political Economy (CHOPE), 2020)
Duke's Center for Interdisciplinary Studies in Science and Cultural Theory (CISSCT) hosted a two-year program on "Science Studies and Economics" from 2018-2020. This is a draft of a talk that was to be given in that program in March 2020, but was cancelled with Duke's coronavirus closure. Written for a general audience, the talk was not directed to economists, philosophers of economics, or historians of economics, but rather toward attendees affiliated with CISSCT. The talk historicizes the difficult relationship between economics and science studies. The absence of detailed references is a result of the talk's informal nature.
Keywords: A1; B2; B4; Y8; 330; science and technology studies; sociology of scientific knowledge; science wars; neoliberalism